A Strategy for Protecting Youth from Modern Threats Based on the Teachings of Imam Abu Mansur Maturidi (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article analyzes the theoretical and methodological foundations for protecting today’s youth from religious extremism, terrorism, ideological emptiness, and harmful influences based on the teachings of Imam Abu Mansur Maturidi. It includes quotations from Maturidi’s works and provides a deep philosophical, social, and scientific justification for their relevance in the modern era. The article puts forward new ideas and explores issues not yet addressed in the current literature.